A clinical student exchange program organized by cardiothoracic department: feedback of participants - Tirilomis, Theodor (BioMed Central, 2013)
BACKGROUND: The development of a student exchange program was an essential part of the cooperation between the Medical Schools of the University of Goettingen (Germany) and the University of Thrace in Alexandroupolis (Greece). The student exchange program started in 2008 and was performed once a year. The experiences of this program and the feedback of participants are presented. METHODS: Although organized by the Dept. of Thoracic, Cardiac, and Vascular Surgery, the approach of the program was multidisciplinary. Participants also attended Continuous Medical Education activities primary addressed to physicians. At the end of the program, the participants evaluated the program anonymously. The educational units were rated via a 4-grade system. Additionally, it was possible to comment both positive and negative aspects of the program. RESULTS: Twenty-nine educational units were evaluated. The practical teaching units yielded a better result than the classical teaching units (93% of practical units were evaluated as “very good” vs. 74% of lectures/seminars). The Continuous Medical Education activities were evaluated less favorable (only 61% were evaluated as “very good”). CONCLUSIONS: The student exchange program enhanced effective teaching and learning. Courses supporting practical medical skills were extremely positive evaluated. Continuous Medical Education activities are not suitable for students and therefore, we do not include such an event anymore. Additionally, the program created an excellent forum for contact and communication between the students of the two universities.